Experimental demonstration of electric power generation from Earth's rotation through its own magnetic field - Christopher F. Chyba; Kevin P. Hand; Thomas H. Chyba (Physical Review Research)
Earth rotates through the axisymmetric part of its own magnetic field, but a simple proof shows that it is impossible to use this to generate electricity in a conductor rotating with Earth. However, we previously identified implicit assumptions underlying this proof and showed theoretically that these could be violated and the proof circumvented. This requires using a soft magnetic material with a topology satisfying a particular mathematical condition and a composition and scale favoring magnetic diffusion, i.e., having a low magnetic Reynolds number R_{m} [Chyba and Hand, Phys. Rev. Appl. 6, 014017 (2016)2331-701910.1103/PhysRevApplied.6.014017]. Here we realize these requirements with a cylindrical shell of manganese-zinc ferrite. Controlling for thermoelectric and other potentially confounding effects (including 60 Hz and RF background), we show that this small demonstration system generates a continuous DC voltage and current of the (low) predicted magnitude. We test and verify other predictions of the theory: voltage and current peak when the cylindrical shell's long axis is orthogonal to both Earth's rotational velocity v and magnetic field; voltage and current go to zero when the entire apparatus (cylindrical shell together with current leads and multimeters) is rotated 90^{∘} to orient the shell parallel to v; voltage and current again reach a maximum but of opposite sign when the apparatus is rotated a further 90^{∘}; an otherwise-identical solid MnZn ferrite cylinder generates zero voltage at all orientations; and a high-R_{m} cylindrical shell produces zero voltage. We also reproduce the effect at a second experimental location. The purpose of these experiments was to test the existence of the predicted effect. Ways in which this effect might be scaled to generate higher voltage and current may now be investigated.